DIGITAL FOOTPRINTS: UNPACKING CULTURAL IDENTITY THROUGH ENGLISH-LANGUAGE PRACTICES ON SOCIAL MEDIA - Sugiarto, Eko; Arif, M Fauzi (University of Kuningan, 2024)
In an increasingly widespread digital age, the practice of speaking English on social media has become one of the most striking cultural imprints. This phenomenon is not just a form of communication, but also a powerful representation of cultural identity in today's global society. This research aims to dig deeper into the cultural footprints manifested in English-speaking practices on social media, focusing on the representation of cultural identity. This study uses a qualitative approach by analyzing case examples from social media such as Instagram, Twitter, and online discussion forums. The results in this study state that the practice of speaking English on social media reflects the complexity and diversity of cultural identities in today's global society. The use of English is not only as a means of communication, but also as a medium to convey individual and collective cultural identity. Factors such as an individual's cultural context, social media platforms, demographic factors, globalization, and power dynamics play an important role in shaping the way English is used and interpreted as a representation of cultural identity. Therefore, a deeper understanding of the dynamics of language and culture in this digital age is important to promote appreciation of cultural diversity, as well as to build bridges of understanding and dialogue between different cultural groups